Exploring strategies for the use of mixed microalgae in cellulase production and its application for bioethanol production. (8th April 2022) - Shokrkar, Hanieh; Zamani, Mehdi; Ebrahimi, Sirous
Abstract: Improving the enzymatic hydrolysis processes of cellulosic materials can be considered a key aim for bioethanol production. Cellulase production using mixed microalgae by mono and co‐cultivation of Trichoderma reesei and Aspergillus niger has not yet been reported. In this study, the effect of different concentration ratios of cellulose and microalgae on the production of cellulases was investigated. Media containing equal mass percentages of microalgae and cellulose showed the highest cellulase activity (3.3 U mL −1 ) among other tested ratios using co‐cultivation of fungi. The optimal percentage of microalgae (50%) increased enzyme activity by about 20% compared with pure cellulose due to necessary and rare elements in the microalgae. Subsequently, fermentation of this sample to bioethanol using Saccharomyces cerevisiae demonstrated a yield of 0.46 g ethanol/g glucose (92% of the theoretical value). The microalgae ratio is therefore an important factor and can be optimized to gain the highest enzyme activity and improve the cost‐effectiveness of bioethanol production from microalgae. © 2022 Society of Chemical Industry and John Wiley & Sons, Ltd